Datasets for Electron capture and excitation in H^+ - Li^+ collisions - Jakimovski, Dragan; Ratko K. Janev (My University, 2019)
The data files attached to this paper follows the information presented on the corresponding figures. Some of them contains additional data, regarding state energies and charge transfer sections to higher states, which were not presented in the published version of the paper due to page limitations. In addition to published charge exchange and excitation cross sections we provide unpublished data for direct ionization section, obtained with the adopted basis.
Each data file is an ASCI text file with several lines of comments at their beginning with short explanation for columns, units, missing or otherwise unacceptable data, etc. The independent variable is put in the last column - in this case energy. The name of the file starts with a number, and short explanation of its content for an easy orientation. In the following we list them for convenience of the user. All calculations were performed on HPC at FINKI, Skopje. The authors gratefully acknowledge the support of people in charge of smooth running of the cluster and prof. B. Jakimovski, PhD in particular for helpful advise on many occasions. For further details regarding computations and data itself: dragan.jakimovski@gmail.com
Keywords: atomic and molecular collisions; plasma physics